Knowledge, Representations, Attitudes, and Behaviors of Women Faced With Taking Medications While Breastfeeding: A Scoping Review. (February 2017) - Spiesser-Robelet, Laurence; Brunie, Vanida; de Andrade, Vincent; Gagnayre, Rémi
Background: Breastfeeding is a major public health issue in terms of its benefits to both mothers and infants. Despite recommendations, breastfeeding initiation and duration are low in many industrialized countries. Although human milk is viewed as the most appropriate food for infants, when it is perceived as contaminated, doubts about its quality can lead to negative behaviors concerning breastfeeding. This is especially true when mothers are taking medication. Research aim: The aim of this review is to evaluate the data in the literature on the knowledge, representations, attitudes, and behaviors of women with regard to taking medication while breastfeeding. These elements should aid our understanding of how the mothers' behaviors are constructed in this situation. Methods: The authors conducted a scoping review to map and analyze the available data from literature sources regarding breastfeeding mothers' knowledge, representations, attitudes, and behaviors about medicines. A staged approach to the scoping review was used. Results: Eighteen studies met the selection criteria. They described safety behaviors like noninitiation, duration reduction, breastfeeding cessation, and refusal to take medication in order to breastfeed. Most showed a conflict between taking medication and breastfeeding. Because the knowledge, representations, and attitudes behind such behaviors have received very little study, it is difficult to explain how these behaviors are constructed. Conclusion: The results of this review confirm the need for a qualitative study to explore the knowledge, representations, and attitudes of breastfeeding women faced with taking medications, so that we can understand their connection with observed behaviors and take appropriate educational action.